The Influence of Servicescape on Repurchase Intention at Salejourn Cafe and Space Padang - Abdul Hamid; Kurnia illahi Manvi (Pt. Threeple Herphi Educate, 2025)
This study investigates the influence of servicescape on repurchase intention at Salejourn Café and Space Padang, motivated by fluctuating transaction volumes and customer complaints regarding ambient conditions, layout, and noise levels that may hinder customer loyalty. Employing a quantitative approach with a causal associative design, data were collected through a structured questionnaire administered to 105 respondents who had visited the café within the past three months. The instrument consisted of 24 items measured on a five-point Likert scale and was tested for validity and reliability, confirming strong construct validity and internal consistency. Data analysis was performed using SPSS 26.0, including descriptive statistics, assumption testing, and simple linear regression. The findings reveal that the servicescape was generally rated good (mean score 68.3%), while repurchase intention was categorized as fairly good (mean score 63.9%). Regression results indicate that servicescape has a positive and significant effect on repurchase intention, with a regression coefficient of 0.725 (p < 0.05) and an R² value of 0.465, meaning that servicescape explains 46.5% of the variance in repurchase intention. These results demonstrate that well-designed physical environments, particularly spatial layout and symbolic elements, enhance customer satisfaction and loyalty, while highlighting the need for improvements in ambient conditions. Theoretically, this study contributes to the literature on consumer behavior in hospitality, and practically, it provides insights for café managers to optimize servicescape design to sustain competitiveness and strengthen repurchase intentions.